Pengaruh Employability Skill dan Pengalaman Magang Terhadap Kesiapan Kerja Mahasiswa Manajemen Universitas Riau - Audra Bianka Faisal; Susi Hendriani; Dian Puspita Novrianti (AKSIOMA : Jurnal Manajemen, 2025)
This research was conducted to study the influence of employability skills and internship experience on the work readiness of undergraduate management students from the Class of 2021 at the Faculty of Economics and Business, Riau University. The population in this research consisted of management students from Class 2021 who had completed an internship, totaling 287 people, with a sample of 167 individuals determined by the purposive sampling technique. The research prove that employability skill and internship experience have a positive and significant effect simultaneously on work readiness, employability skill has a positive and significant effect on work readiness, and internship experience has a positive and significant effect on work readiness. So that increasing employability skill and internship experience will increase student work readiness.